PENGAWASAN PENCEMARAN LINGKUNGAN OLEH DINAS LINGKUNGAN HIDUP KABUPATEN ROKAN HILIR (STUDI KASUS PT.BALAM SAWIT SEJAHTERA) - Frans Romario Pardede; Harapan Tua RFS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The development of the industrial sector also has a negative impact. The importance of supervision of oil palm companies is carried out to protect the environment so that it is free from pollution that can be detrimental. Environmental pollution carried out by PT.Balam Sawit Sejahtera that occurred in the area of Rokan Hilir Regency certainly shows that the effectiveness of supervision in the Rokan Hilir District Environmental Office has not been maximized. The purpose of this research is to see how the supervision of environmental pollution by the Environmental office of Rokan Hilir District (case study PT. Balam Sawit Sejahtera) and any factors that become a barrier to the supervision of pollution by the Environment Office of Rokan Hilir District. This research was conducted in Pekanbaru City using qualitative descriptive methods, data collected through observation and interviews.. The theory used in this study is Sukanto's theory in which a good oversight step is to determine the standards of supervision, conduct research into surveillance objects, and perform corrective or sanctions actions against breach of provisions. The results of this study indicate that pollution control by the Rokan Hilir District Environmental Agency is not optimal, the lack of time standards in conducting direct supervision to the field is considered ineffective and also inhibiting factors in environmental pollution monitoring conducted by the Rokan Regency Environmental Agency Downstream is in terms of experts the number of supervisors, equipment assignments and operational costs..  Keywords : Supervision, Environmental Pollution, Environmental Agency